One-Pot Approach for SNAr Reaction of Fluoroaromatic Compounds with Cyclopropanol - Jin, Hao; Gao, Zhuo; Zhou, Shaodong; Qian, Chao (Synlett, 2019)
A novel method for preparing aromatic compounds containing cyclopropoxy via nucleophilic aromatic substitution reaction (SNAr) of fluoroaromatic compounds with cyclopropanol under relatively mild conditions is presented. As compared to the approaches reported previously for preparing 1-(cyclopropyloxy)-2-nitrobenzene, the one proposed in this work is simplified without sacrificing the yields: When the reaction was performed at 75 °C with Cs2CO3 as the base and DMF as solvent, after 6 h the yield was up to 90%. Finally, various fluoroaromatic compounds were employed as substrates for a test that proves a wide application scope of the method.
Keywords: fluoroaromatic compounds; nucleophilic aromatic substitution reaction (SNAr); cyclopropanol; Cs2CO3; DMF